2017
DOI: 10.3928/01477447-20170223-01
|View full text |Cite
|
Sign up to set email alerts
|

Using Accelerometer-Based Portable Navigation to Perform Accurate Total Knee Arthroplasty Bone Resection in Asian Patients

Abstract: Implant alignment is an important factor affecting clinical results associated with total knee arthroplasty (TKA). No report exists showing the utility of an accelerometer-based portable navigation system among patients with marked femoral bowing. The aim of this study was to evaluate the accuracy of a portable navigation system for implant alignment in Asian patients with marked femoral bowing. The authors evaluated 142 consecutive TKAs performed for primary osteoarthritis since July 2013. A portable navigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 39 publications
1
39
1
Order By: Relevance
“…[8][9][10][15][16][17][18][19][20][21][22][23][24] Among the included studies, six were RCTs, 8,10,17,19,21,23 one was a prospective study, 16 and six were retrospective studies. 9,15,18,20,22,24 The present meta-analysis analyzed 1,454 patients with 1,551 TKAs (mean sample size, 119.31 TKAs per study). None of the included studies contained revision or failure cases.…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[8][9][10][15][16][17][18][19][20][21][22][23][24] Among the included studies, six were RCTs, 8,10,17,19,21,23 one was a prospective study, 16 and six were retrospective studies. 9,15,18,20,22,24 The present meta-analysis analyzed 1,454 patients with 1,551 TKAs (mean sample size, 119.31 TKAs per study). None of the included studies contained revision or failure cases.…”
Section: Search Resultsmentioning
confidence: 99%
“…Eight studies with nine groups reported a tibial component alignment out of AE3 degrees [8][9][10]15,16,19,22,24 ; the pooled result indicated that PAD was better than CON with significant differences (OR, 0.56; 95% CI, 0.33-0.93; p ¼ 0.02; outlier percentage, PAD/CON ¼ 5.36%/10.00%) (►Fig. 2A).…”
Section: Alignment Outliers Out Of Ae2 or Ae3 Degreesmentioning
confidence: 99%
See 3 more Smart Citations